(untitled) (Journal of Economic Research & Business Administration, 2016)
Relevance of the degree of financial leverage of enterprises is considered. Definition of financial leverage is given. The significance of financial leverage in enterprises is described. Key concepts of degree of financial leverage of enterprises are given. Methods of european and american concepts of the degree of financial leverage are shown. Analysis of these concepts is given. Practical application of european concept of financial leverage evaluation in Kazakhstan and practical application of american concept of financial leverage evaluation in China are considered. And as theoretical formulas are not fully sitisfied with practical situations in these two countries, there is a necessity to take into account unaccounted factors. Adjusted formulas of european concept on the basis of real situation in Kazakhstan and american concept on the basis of Chinese practice are worked out.